The Chemistry of Hyperalkaline Springs in Serpentinizing Environments: 1. The Composition of Free Gases in New Caledonia Compared to Other Springs Worldwide. Issue 9 (14th September 2021) - Monnin, Christophe; Quéméneur, Marianne; Price, Roy; Jeanpert, Julie; Maurizot, Pierre; Boulart, Cédric; Donval, Jean‐Pierre; Pelletier, Bernard
Abstract: Serpentinization is a natural process that transforms ferromagnesian minerals such as olivine into serpentine and that produces waters at very high pH and gases enriched in methane (CH4 ) and hydrogen (H2 ). We report the composition of gases venting at two springs (Bain des Japonais and Rivière des Kaoris) of the serpentinizing environment of the Prony Bay (New Caledonia) collected eight times between 2011 and 2014, along with in situ measurements (temperature, pH, oxydo‐reduction potential, dissolved oxygen content) of on‐land alkaline springs of the Southern New Caledonia ophiolite. Venting gases are mainly composed of H2, CH4, and N2 and their composition has slightly varied during the 4‐year field survey. An elevated oxygen (O2 ) content in a high‐pH water sample is due to air uptake during surface flow. O2 ‐corrected gas compositions along with those published for gas data obtained at similar serpentinizing environments (Italy, Turkey, Philippines, and Oman) show that the H2 and CH4 concentrations display a linear correlation with a slope close to the value corresponding to the CH4 production from carbon dioxide rather from a less oxidized carbon such as carbon monoxide. Although these data are consistent with the stoichiometry of the Sabatier reaction, as such in the gas phase, it is also possible that microbial hydrogenotrophic methanogenesis takes place in the aqueous phase followed by degassing. A diagram is proposed that outlines the partitioning of H2 and CH4 between the gaseous and aqueous phases and the need to consider a two‐phase flow in the hydrology of these hyperalkaline environments. Plain Language Summary: Serpentinization is a natural process that transforms ferromagnesian minerals such as olivine into serpentine. This process is accompanied by the formation of high‐pH water, hydrogen, and methane. This forms a unique ecological niche for microorganisms adapted to extreme pH and/or involved in the hydrogen and/or methane cycles. There is an ongoing debate on the mechanisms at play and on the contribution of abiotic versus biogenic reactions. An analysis of the composition of free gases collected in hyperalkaline springs of New Caledonia combined with literature values for similar sites worldwide shows that the formation of methane follows the stoichiometry of a Sabatier‐type reaction involving fully oxidized carbon (CO2 ) and not carbon monoxide (CO) as required by a Fischer‐Tropsch‐Type process. Although it could be concluded that methane production occurs in the gas phase, and as such would be abiotic, it does not rule out the possibility that the relationship between gaseous hydrogen and methane is due to methane production and hydrogen consumption by microorganisms in the aqueous phase followed by degassing. Key Points: Hyperalkaline spring waters are anoxic. An elevated high O2 content in free gases results from air contamination The relationship between H2 and CH4 contents of free gases is consistent with the conversion of fully oxidized carbon (CO2 ) The H2 ‐CH4 relation is consistent with a Sabatier reaction in the gas or methane production by hydrogenotrophic methanogens in the water